Da’wah Values in Intercultural Communication and Local Wisdom within the Baduy Tribe Community - Holilah, Ilah; Heryatun, Yayu; Rohmawati, Cucum; Effendi, Dudy Imanuddin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This research aims to explore da'wah values in the interactions of the Baduy community with others who possess different cultural values and their local wisdom in facing the challenges of modernity. The method used in this research was qualitative. The research subjects were the outer and inner Baduy communities. Data was collected through direct observation, interviews, and documentation. Data validity was ensured through triangulation. The results of the research indicate that da'wah values in the Baduy community are manifested in their inclusive attitude and hospitality when communicating with people outside of Baduy. The Outer Baduy community acts as a filter for external values, carefully selecting to preserve positive local cultural values. Meanwhile, the people of Inner Baduy represent the original Baduy (Tangtu) and demonstrate the values of da'wah through their responsibility in preserving traditions, culture, and local values. Their obedience to ancestral laws, tribal leaders, and local wisdom functions as tools in dealing with the challenges of modernity.